DAMPAK DEGRADASI LINGKUNGAN TERHADAP TRANSPORTASI SUNGAI MAHAKAM - Tambunan, Efendy (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The River Mahakam has a big role for citizen who live in the East Kalimantan region. This river is as the barometer of a natural balance in this area. At present, all of upstream regions of the River Mahakam were converted from the forest areas to  palm plantations and coal mining in massive scale. Its impact, the River Mahakam has a big sedimentation and decreasing discharge of water. In order to understand how big the impact of its problem to sustainaibility of river transportation, the research has conducted to calculate sedimentation and the discharge of water into the River Mahakam with descriptive method. The research showed that sedimentation has increased and the discharge of water has decreased into the River Mahakam. This problem has been threatening sustainability the River Mahakam as waterway.